KOMPONEN HASIL DAN KANDUNGAN KARBOHIDRAT EMPAT KULTIVAR SORGUM (Sorghum bicolor(L.)Moench) DENGAN JARAK TANAM YANG BERBEDA - Septian Edi Siswanto; Elza Zuhry; Nurbaiti Nurbaiti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The objective of this research was to determine the effect of different spacing of the components and the results of carbohydrate content and find out proper plant spacing for each sorghum cultivars. This research was conducted at the Agriculture experiment station and in the plant breeding laboratory, Riau University from April 2015 to Agustus 2015. Research conducted as an experiment using a randomized block design (RAK), which consists of two factors and three replications, The first factor was sorghum cultivar which consists of Patir 9, Patir 10, Pahat  and Mandau. The second factor was spacing of which is comprised of a spacing of 75 cm x 15 cm, 75 cm x 20 cm and 75 cm x 25 cm. Observational data were analyzed statistically using analysis of variance. The parameters were observed amongtime to harvest, panicle length, seed weight per panicle, seed weight per m2, weight of 1000 seeds, harvest moisture content and carbohydrate content. The results showed that sorghum cultivars with a narrow  spacing (75 cm x 15 cm), middle (75 cm x 20 cm) and distantly (75 cm x 25 cm) not accelerate time to harvest, do not increase the yield component that seed weight per m2 and weight of 1000 seeds, as well as harvest moisture content and carbohydrate content. Mandau cultivars with spacing distantly (75 cm x 25 cm) have tended to be higher carbohydrate content that is 85.12% compared to the three other cultivars. Cultivars Patir 9 at narrow spacing (75 cm x 15 cm) have the results tend to be more that 4.1 tonnes/ha compared to the three other cultivars. Keywords: sorghum cultivars, plant spacing, yield components and carbohydrate content